The wood mouse Sylvaemus tauricus (Mammalia) in the south of Ukraine: limits and features of distribution in a historical biogeographical context - Zagorodniuk, I. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
The article analyses the specifics of distribution of the species Sylvaemus tauricus in the south of Ukraine, particularly in the coastal regions, where it reaches the northern limits of the steppe natural zone. The number of records describing the southern limit of distribution in the continental part of the range (i.e., outside the Crimea) is generally not large (about 30), but all of them eloquently testify to some common features. The first is that the species penetrates deep into the steppe zone, essentially to the border between the northern (gully) and southern (driest) steppe. Secondly, the species demonstrates the possibility and high speed of forming new populations, including banded populations, in areas of expansion, both along natural eco-corridors (primarily along rivers) and using artificial eco-networks (forest belts, roadside or canal-side tree and shrub strips). Thirdly, there is a unified front of habitats, which indicates that the range corresponds to the natural zonation. Comparison of the obtained distribution scheme with the forestry zonation of Ukraine shows that the species is completely absent in the zone of dry (treeless) steppes, which belong to the Black Sea–Pryazovia South Steppe District. However, the boundary is even more northern: it runs along the middle of the Northern Steppe District (bayrak steppe zone), in some places with the species crossing the southern border of this district. Available data indicate the species’ expansion to the south, which may be due to the spread of artificial stands, both of stripe-type (forest belts and stands along water canals, railways, and highways) and focal-type (forest park areas around settlements, artificial forests, etc.). One of the signs of expansion is the increasing share of the species in captures in different types of stands: in Luhansk Oblast, the share of this species in places of its occurrence has gradually increased from 0.64% in 1957–1965 to 13.8% in 2002–2014. The southward expansion of this wood mouse species is in contrast with the trend of the natural zones shifting northward, which demonstrates the importance of non-natural habitats in species dispersals. The hypotheses of the connection between the mainland range of the species and the Crimean isolate are discussed. It is assumed that the species’ range in the coastal regions has undergone repeated pulsations with the formation of a continuous distribution of the species. Nevertheless, it is possible that the species could have entered the Crimea from the Western Caucasus during the period of sea level regression and the formation of the Kerch–Taman land bridge.